2010
DOI: 10.1089/ten.tec.2009.0785
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production of Red Blood Cells in Suspension by Electrostatic Interactions with Culture Plates

Abstract: Enucleation of erythroblasts, a critical step in the generation of red blood cells (RBCs), occurs at a low rate without cocultured stromal cells. Previously, the surface properties of the cell culture plate were not considered in the enucleation process, because the cells exist in suspension. Here, we show that a significantly higher rate of enucleation of erythroblasts occurred on the positively charged plates than on the negatively charged surfaces or the both negatively and positively charged plates. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…The hybrid (N‐ and O‐) plasma treated Primaria™ was found to display even slightly (but statistically significant, p < 0.05) better performance than TCP, suggesting that the combination of O‐ and N‐containing moieties might constitute the new “gold standard” for cell culture dishes. This would agree with earlier‐published observations by several groups …”
Section: Resultssupporting
confidence: 94%
“…The hybrid (N‐ and O‐) plasma treated Primaria™ was found to display even slightly (but statistically significant, p < 0.05) better performance than TCP, suggesting that the combination of O‐ and N‐containing moieties might constitute the new “gold standard” for cell culture dishes. This would agree with earlier‐published observations by several groups …”
Section: Resultssupporting
confidence: 94%
“…Baek et al 12 similarly reported that an amine-rich versus an uncharged substrate augmented the number of enucleated erythroid cells, and hypothesized that electrostatic interactions between the cell membrane and the positively charged substrate were responsible. In addition, the investigators suggested an enucleation mechanism by which the direction of enucleation was upward, but no directly supportive evidence was provided.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Furthermore, surfaces incorporating primary versus tertiary amines more effectively induced enucleation during the erythroid differentiation of HSCs. 12 However, highly cytotoxic 3-aminopropyl trimethoxylsilane (APES) was utilized during the amine group incorporation. In addition, the amine group density was not optimized for HSC expansion and enucleation during erythroid differentiation, and the underlying mechanism for the interaction between the HSCs and the investigated substrates remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Baek et al [87] proposed an ingenious method to enhance enucleation rates by positively charging the tissue culture plates. These publications emphasize the importance of identifying the best material for erythroid cultures and show that targeted modifications of the material can improve the results.…”
Section: State-of-the Art In Large-scale Blood Productionmentioning
confidence: 99%